(untitled) (Community Based Medical Journal, 2025)
The relationship between diabetes and cardiovascular risk is closely linked to dyslipidaemia, a condition where there is an abnormal amount of lipids (cholesterol, triglycerides, etc.) in blood. In female diabetic patients, understanding the lipid profile is essential due to the unique physiological and hormonal differences compared to males. A cross-sectional, descriptive study was carried out in the Department of Physiology, Mymensingh Medical College, Bangladesh, between July 2016 and June 2017, to see the cholesterol levels in type 2 diabetes mellitus female patients and compare with that of normal subjects. A total of 210 subjects were selected. They were grouped as control group (group-I) consisting of 70 healthy females of reproductive age, (21-45 years) and study group (group-II), which was again subdivided to group-IIA (70 diabetic females of reproductive age, 21-45 years) and group-IIB (70 diabetic females of post-menopausal age, 45-70 years). Estimation of serum cholesterol was done by enzymatic colorimetric method. The mean serum total cholesterol in group I, group IIA and group IIB were found 171.05±12.07 mg/dl, 217.75±36.87 mg/dl 239.28±48.01 mg/dl respectively. The difference between group I and group IIA was found statistically highly significant (p<0.0001). Similarly, the difference between group IIA and group IIB was also statistically significant (p<0.05). Our data suggests that serum total cholesterol observed in control group of normal healthy females was within normal physiological range. However, in type 2 diabetic females, both in reproductive age group and postmenopausal group, serum total cholesterol levels were found elevated. CBMJ 2025 January: Vol. 14 No. 01 P: 61-65